Surface analysis : the principal techniques - Vickerman, John C., ....- (Chichester : Wiley, 2006)
Vacuum Technology for Applied Surface Science (R Wilson) Electron Spectroscopy for Chemical Analysis (B Ratner & D Castner) Auger Electron Spectroscopy (H Mathieu) Secondary Ion Mass Spectroscopy-the Surface Mass Spectrometry (J Vickerman & A Swift) Low-Energy Ion Scattering and Rutherford Backscattering (E Taglauer) Vibrational Spectroscopy from Surfaces (M Pemble) Surface Structure Determination by Interference Techniques (W Flavell) Scanning Tunnelling Microscopy and Atomic Force Microscopy (G Leggett) Index.
Keywords: Grensvlakchemie; Materiaalonderzoek; Meettechnieken; Oppervlakte-analyse.